An Assessment of Dam Water Quality for Fish Production in Malkerns, Eswatini - Vilane, Dr. Bruce ROY Thulane; Ncongwane, Ntokozo; Mkhwanazi, Mkhwanazi (European Journal of Applied Sciences, 2021)
The construction of dams always provided an opportunity to promote commercial fish farming. In a number of dams commercial operations could be sustainably accommodated. However, there is a lack of assessment in the water quality of these water bodies for their suitability for fish production, though water quality is a critical aspect for fish production. Dams can provide the water needed for various applications in arid and semi-arid environments. However, most of these water sources are polluted with pollution from various sources including agriculture. An experiment was carried out to assess the quality of the Malkerns Research Station Dam water for fish production. The water from the inlet and outlet of the dam were used as the treatment, which was replicated three times. The fish farming production water quality guidelines were used as a control. Sampling was conducted in the morning using the grab sampling technique to collect water from the dam. The samples were taken to the laboratory for testing. Data analysis was conducted using one-way ANOVA in SPSS version 2.0 computer software. The results reflected that the mean pH of the water in the inlet and outlet of the dam was 6.9 and 6.7, respectively, which was within the recommended pH water quality guideline (6.5 - 9.0) for fish production. The mean turbidity of the dam water ranged from 3.8 NTU to 5.6 NTU, which was below the recommended water quality guideline value of 25 NTU for fish production. The mean salinity of the dam water was 400 mg/L, which was within the recommended water quality guideline (0 – 600 mg/L) for fish production. The mean copper level of the water in the inlet and outlet of the dam was 0.016 mg/L and 0.006 mg/L, respectively, which was higher than the recommended water quality guideline value of 0.005 mg/L for fish production. Based on the heavy metals, it was concluded that the Malkerns dam water quality was not suitable for fish production.